Seasonal Shift of the Diurnal Cycle of Rainfall Over Medellin's Valley, Central Andes of Colombia (1998–2005) - Bedoya-Soto, Juan Mauricio; Aristizábal, Edier; Carmona, Alejandra M.; Poveda, Germán (Frontiers in Earth Science, 2019)
The spatiotemporal variability of precipitation in regions of complex mountainous terrains constitutes one of the most challenging research topics of geosciences. This paper explores hourly precipitation data from a set of 25 stations spanning the period 1998 to 2005 within northwestern Colombia, in the Aburrá Valley and the neighboring San Nicolás plateau (75.16W-6N and 75.66W-6.6N) which accounts for a land area of approximately 4000 km2. Our aim is to identify the main features of the diurnal cycle of precipitation over this complex terrain. We found that the average diurnal cycle of rainfall in the study region is bimodal at regional scale although it results from the superposition of two unimodal diurnal cycles shifting its phase throughout the seasons of the year. From October to April, average diurnal rainfall peaks in the afternoon hours (13:00-16:00 LST) but from May to September, the phase of the diurnal cycle changes to midnight hours (22:00-02:00 LST). Three low-level jets (LLJs), namely Caribbean, CHOCO, and the so-called Corriente de los Andes Orientales (CAO), are relevant to explain the seasonal shift of the diurnal cycle given their modulation of the seasonal variation of moisture sources and transport over this region. During June-July-August, moisture from afternoon evaporation processes at the bottom of the inter-Andean Magdalena Valley, located at the east of the study region, is transported by anabatic and easterly trade winds and contribute to explain the midnight and early morning peak. The life cycle of convective processes influences the orographic nature of rainfall distribution and timing in the region since deep convective cores are related with the afternoon peak, whereas wide convective cores with the early morning peak.